Perlindungan Hukum Bagi Anak Bawaan Warga Binaan ‎ Di Lembaga Pemasyarakatan Perempuan ‎ Kelas IIA Kerobokan - Luh Kadek Linda Marsiari; Deli Bunga Saravistha; I Gusti Ngurah Aristiawan (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
Newly born babies are highly dependent with their parents in meeting their needs, thus they cannot be separated, especially with the mother. The right fullfilment of women prisoner’s children is highly affected by the deprivation of the mother’s right. The purpose of this study is to find out the implementation as well as the challenges of the regulation in Lembaga Pemasyarakatan Perempuan (LPP) Kelas II A Kerobokan in an attempt to fulfill the rights of women prisoner’s children. The primary data that is used in this study are the interview results with woman prisoners and LPP officers. Meanwhile, the secondary data is collected from literature studies and from Indonesia Law and Regulation. Furthermore, the research methodology that is used in this study is empirical research method, while the data analysis method is descriptive qualitative method. The result of this study shows the legal protection for the right of women prioner’s children in LPP Kelas II A Kerobokan has been well implemented according to the Standard Operating Procedure (SOP), however still needs to be maximized. The challenges encountered includes infrastructure, human resources and teamwork.